Effectiveness of clinical teaching practices of preceptors in three referral hospitals at Stung Treng Region, Cambodia - Yung Narem
This study described students? perceptions on the effectiveness of clinical teaching practices of preceptors. Preceptorship programs are designed to provide competent clinical teaching, evaluation, provision of appropriate feedback and support, provision of opportunities for working as multidisciplinary team members, development of interpersonal relationships, theory-practice integration and clinical competence developments of Associate Degree in Nursing and Midwifery students through supervision of the preceptors. Unfortunately, Associate Degree in Nursing and Midwifery students often complain that their preceptors did not provide: enough feedback through clinical procedures, pre-post clinical conferences, case presentations, or small group discussion; monitoring and supervision during practicum that impacts bedside teaching and management of patient problems; good preparation for formal clinical teaching; and opportunities for applying the nursing process. This cross-sectional survey was conducted to (1) describe the level of effectiveness of clinical teaching practiced by preceptors at three referral hospitals (Stung Treng, Kratie, and Ratanakiri) in Stung Treng region, Cambodia, as perceived by students in the following areas: a) nursing expertise, b) teaching competence, and c) interpersonal relationship skills, and (2) identify characteristics (gender, ae, program, and year level) that are associated with effective clinical teaching. A cross-sectional survey was used. The sample was composed of 158 students of the Associate Degree in Nursing (ADN) and Associate Degree in Midwifery (ADM) programs year 2 and 3 who have clinical exposure under preceptors. Responents were chosen using random sampling from nursing and midwifery students who have practiced at Stung Treng Referral Hospital (69), Kratie Referral Hospital (105), and Ratanakiri Referral Hospital (86). The Clinical Teaching Evaluation (CTE) Questionnaire developed by Fong & McCauley, 1993 was administered to determine students? perceptions on the effectiveness of clinical teaching practices of preceptors in terms of Nursing expertise, Teaching competence, and Interpersonal relationship skills. The 25 Clinical Teaching Evaluation (CTE) was ranked on a five-point scale from one (Strongly Disagree) to five (Strongly Agree). Frequency counts and percentage distributions, as well as descriptive statistics were applied such as the mean, standard deviations, ANOVA, and Chi-Square test. The Reliability Statistics of Cronbach?s Alpha Coefficient?s overall mean scores for all items were 0.739. The findings of mean rating scores to the effectiveness of clinical teaching practices of preceptors had a high mean = 3.63 and SD = 1.00. Specific mean ratings that were rated highly effective clinical teaching practices were nursing expertise (Mean = 3.72, SD = 0.91), teaching competence (Mean = 3.51, SD = 1.06) and interpersonal relationship skills (Mean = 3.65, SD = 1.02). This study indicated that gender, age, program, and year level are not associated to the effectiveness of clinical teaching practices of preceptors. The clinical teaching quality of preceptors needs to be improved by preceptorship course training with appropriate teaching methods. The effectiveness of clinical teaching practices that are most important to assist students obtain clinical competence to be qualified nurses and midwives must be given emphasis.